2020
DOI: 10.1038/s41598-020-66871-4
|View full text |Cite
|
Sign up to set email alerts
|

High Adsorption of Benzoic Acid on Single Walled Carbon Nanotube Bundles

Abstract: Removal of harmful chemicals from water is paramount to environmental cleanliness and safety. As such, need for materials that will serve this purpose is in the forefront of environmental research that pertains to water purification. Here we show that bundles of single walled carbon nanotubes (SWNTs), synthesized by direct thermal decomposition of ferrocene (Fe(C5H5)2), can remove emerging contaminants like benzoic acid from water with high efficiencies. Experimental adsorption isotherm studies indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…A separate work that was recently completed tackles the adsorption energy implications of CNT surface curvature in single-walled and multiwalled arrangements. 37 The net surface charge of the current pristine CNT (0% functionalization) is kept neutral by assigning a van der Waals potential only to carbon atoms. However, carboxyl attachments in the other three cases (1%, 5%, and 10% functionalization) induce local electrostatics.…”
Section: Resultsmentioning
confidence: 99%
“…A separate work that was recently completed tackles the adsorption energy implications of CNT surface curvature in single-walled and multiwalled arrangements. 37 The net surface charge of the current pristine CNT (0% functionalization) is kept neutral by assigning a van der Waals potential only to carbon atoms. However, carboxyl attachments in the other three cases (1%, 5%, and 10% functionalization) induce local electrostatics.…”
Section: Resultsmentioning
confidence: 99%
“…9 This has motivated the usage of nanomaterials such as SC electrodes due to their large specific surface area (SSA). 10 Particularly, carbon-based nanomaterials such as activated carbon, carbon nanofibers, mesoporous carbon, diamond-like carbon, carbon nanotubes (CNTs), graphene, and carbide-derived carbon are used widely. 1,11,12 With the emergence of flexible and portable devices, attention on flexible SCs has increased due to their numerous applications in wearable electronics, smart garments, and so forth.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In both cases, the surface area of the electrode material of an EDLC, therefore, plays an important role because it can be generally said that the higher the surface area, the higher the capacitance will be . This has motivated the usage of nanomaterials such as SC electrodes due to their large specific surface area (SSA) . Particularly, carbon-based nanomaterials such as activated carbon, carbon nanofibers, mesoporous carbon, diamond-like carbon, carbon nanotubes (CNTs), graphene, and carbide-derived carbon are used widely. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers have shown that single-walled nanotubes synthesized by the thermal decomposition of ferrocene (Fe(C 2 H 5 ) 2 ) are able to efficiently remove benzoic acid with higher efficiencies than multi-walled nanotubes. Through simulation studies of molecular dynamics, they have shown that the high efficiency of single-walled carbon nanotubes is attributable to sites with high bonding energy [ 36 ].…”
Section: Introductionmentioning
confidence: 99%